Service Computing System Engineering Life Cycle - Suhardi Suhardi; Novianto Budi Kurniawan; Jaka Sembiring (IAES Indonesia Section, 2017)
The development of service computing technology has triggered the need for organizations to build a service computing system. This system is able to deliver IT services that can meet the challenges and needs of business services. An understanding of the service computing systems engineering life cycle is necessary to model and build the systems. This paper conducts the study of the service computing systems concepts and proposes the life cycle of service computing system engineering. First, some publications relevant to the service computing systems are reviewed systematically in order to develop fundamental concepts and elements of the systems. Second, a metamodel of service computing systems is built based on those concepts. Third, the life cycle model of service computing systems engineering is proposed based on the metamodel. Finally, the verification of the life cycle is conducted by comparing the proposed life cycle to the life cycle of software engineering, service engineering, and service system engineering. The contribution of this paper is to provide a coincise understanding of the components that are needed to build such systems and show the interaction and collaboration between the components in the service computing systems.